Optimalisasi Fungsi Reserse Kriminal dalam Menangani Tindak Pidana Pemerasan di Kepolisan Sektor Belawan - Hutapea, Marlon Dobik; Zulyadi, Rizkan; Ramadhan, M. Citra (Mahesa Research Center, 2022)
The purpose of this study was to determine the function of the criminal investigator, barriers to implementation and the relationship of law enforcement carried out by the Belawan Sector Police with Community Culture in overcoming the crime of extortion in the Belawan area. The type of research used is normative juridical (legal research) by examining various formal legal rules, which are then linked to the research objectives. Sources of data used are secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. The results of the study found that the Medan Belawan Police in carrying out the law enforcement function of the Police and implementing the protection function had several strategies/criminal policies in overcoming the rampant criminal acts of extortion, both preventive and repressive efforts. The obstacles faced by law enforcement can be divided into internal and external barriers. Internal barriers and external barriers. The relationship between criminal law enforcement is not only pursuing the principle of formal law enforcement, but if there is room or opportunity to prevent criminal acts from happening, this is certainly better to implement. This means that the police protection function must be maximized through programs to prevent the occurrence of criminal acts in the community.